1959
DOI: 10.1161/01.res.7.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Stretch Reflexes from the Dog's Lung to the Systemic Circulation

Abstract: Evidence is presented that reflex systemic vasodilatation occurs after stretching dog's lungs by either mechanical traction or positive pressure ventilation under conditions of separate pulmonary and systemic perfusion. This reflex is mediated by the vagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

1962
1962
1986
1986

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 5 publications
5
23
0
Order By: Relevance
“…5, and it shows that the effects on the cardiovascular system produced by inflation of the lungs were markedly lessened by interruption of the vagus nerves. DISCUSSION Partly in confirmation of previous findings (6,7) the results of the present investigation clearly indicate that pulmonary stretch receptors do affect cardiovascular function, and that their activation results in reflex inhibition of sympathetic tone with consequent decreases in myocardial performance, heart rate, and peripheral vascular resistance. That these observed depressor responses are indeed reflex in nature rather than the result of mechanical effects produced by inflation of the lungs is indicated by the fact that they were observed in animals on right heart bypass, which means that they were not merely the result of induced changes in venous return, since blood flow into the pulmonary artery was kept constant.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…5, and it shows that the effects on the cardiovascular system produced by inflation of the lungs were markedly lessened by interruption of the vagus nerves. DISCUSSION Partly in confirmation of previous findings (6,7) the results of the present investigation clearly indicate that pulmonary stretch receptors do affect cardiovascular function, and that their activation results in reflex inhibition of sympathetic tone with consequent decreases in myocardial performance, heart rate, and peripheral vascular resistance. That these observed depressor responses are indeed reflex in nature rather than the result of mechanical effects produced by inflation of the lungs is indicated by the fact that they were observed in animals on right heart bypass, which means that they were not merely the result of induced changes in venous return, since blood flow into the pulmonary artery was kept constant.…”
Section: Resultssupporting
confidence: 92%
“…This conclusion is consonant with the observations of Salisbury et al (6) and Daly et al (7) who studied the effects of the pulmonary stretch reflex on the total systemic vascular bed. The marked diminution in the depressor effects after vagotomy further supports the contention that they are the result of a reflex rather than the consequence of mechanical changes produced in the circulation as a result of inflation of the lungs.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…They concluded on the basis of plethysmographic studies that this response was due to vasodilatation. Salisbury, Galletti, Lewin & Rieben (1959), using a preparation in which the systemic circulation was perfused at constant blood flow, found that inflation of the lungs caused a reduction in systemic arterial perfusion pressure. They did not find any correlation between the size of the response and the inflation pressure and reported no values for the inflation volumes used in their experiments.…”
Section: Introductionmentioning
confidence: 99%